2017
DOI: 10.1063/1.4997257
|View full text |Cite
|
Sign up to set email alerts
|

Note: Progress on the use of MgB2 superconducting joint technique for the development of MgB2 magnets for magnetic resonance imaging (MRI)

Abstract: This note presents a superconducting joint technique for the development of MgB magnetic resonance imaging (MRI) magnets. The MgB superconducting joint was fabricated by a powder processing method using Mg and B powders to establish a wire-bulk-wire connection. The joint resistance measured using a field-decay method was <10 Ω, demonstrating that the proposed joint technique could be employed for developing "next-generation" MgB MRI magnets operating in the persistent current mode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Superconducting joints for both monofilament ,, and multifilament MgB 2 conductors ,,, have been reported. The joints fabricated for multifilament MgB 2 conductors showed inferior performance compared with the joints fabricated for monofilament MgB 2 conductors owing to their finer filament size. ,,, Carbon (C)-doping is usually used in the MgB 2 material to improve its in-field performance. However, the performance of the joints fabricated using C-doped MgB 2 conductors was found to be poorer compared with that of undoped MgB 2 conductors .…”
Section: Introductionmentioning
confidence: 99%
“…Superconducting joints for both monofilament ,, and multifilament MgB 2 conductors ,,, have been reported. The joints fabricated for multifilament MgB 2 conductors showed inferior performance compared with the joints fabricated for monofilament MgB 2 conductors owing to their finer filament size. ,,, Carbon (C)-doping is usually used in the MgB 2 material to improve its in-field performance. However, the performance of the joints fabricated using C-doped MgB 2 conductors was found to be poorer compared with that of undoped MgB 2 conductors .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that joint resistance as low as 5.48 × 10 −15 Ω is achieved for unreacted multifilament MgB 2 wires [22]. It is an aim to maintain the critical current value as well as the low resistance value, in this sense superconducting joints have not been fully optimized yet [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…The superconducting joints of MgB 2 conductors have been reported to be fabricated with both monofilament conductors [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] and multifilament conductors [3,4,8,11,14,[29][30][31][32]. Only a few of these articles reported the performance of joints of reacted MgB 2 conductors [11,20,30].…”
Section: Introductionmentioning
confidence: 99%